Penerapan Model Pembelajaran Problem Based Learning Dalam Upaya Peningkatan Pemahaman Konsep Matematis Siswa Kelas VIII - Mutaqin, Azik; Dewi Susilowati; Andhika Ayu Wulandari (Absis: Mathematics Education Journal, 2025)
This study aims to improve students' understanding of mathematical concepts related to solid shapes with flat surfaces in class VIII A at MTs Al Jauhar Semin Gunungkidul, Semester II of the 2024/2025 academic year, through the Problem Based Learning (PBL) model. The results show an improvement in students' understanding of mathematical concepts, with the initial weighted score of 11 (24.75%) increasing to 20 (45.00%) in Cycle I, 27 (60.75%) in Cycle II, and 35 (78.75%) in Cycle III. The average score also increased from 56.16 in the initial condition to 71.15 in Cycle I, 74.23 in Cycle II, and 84.61 in Cycle III. The number of students who met the Minimum Mastery Criteria (KKM) also rose, from 3 students (11.53%) in the initial condition to 12 students (46.15%) in Cycle I, 16 students (61.53%) in Cycle II, and 25 students (96.15%) in Cycle III. Overall, this study demonstrates that the implementation of the Problem Based Learning model successfully enhanced students' understanding of mathematical concepts related to solid shapes with flat surfaces. Based on these results, it can be concluded that this model is effective in improving students' understanding in mathematics learning.